Mentoring Sebagai Suatu Inovasi dalam Peningkatan Kinerja - Anwar, Zul; Ikawati, Hastuti Diah; Syarifah, Syarifah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Mentoring is a strategy to improve work performance within an organization. This type of research is literature research. Technique of collecting data is done by documentation method that is reading every information that there is relation with study. The data collected from reading results is then analyzed by selecting the appropriate materials or still related to the study. Based on the results of data analysis then synthesized and concluded to be a conclusion of the topic under study. The result of the mentoring process is intentional, does not happen by chance. The key to ensuring the desired outcomes and the sustainability of the mentoring process is to use all the best practices of human performance technology in the needs assessment, planning, design, implementation, and evaluation phase. Mentoring must be closely linked to the organization's mission, objectives, and strategy priorities. Only an integrated quality, capable of facilitating the process associated with current and future missions that can be expected to deal with exposure to the winds of change. The rapidly changing environment demands multi-skilled, flexible workers, and the level of mastery of core competencies. A mentoring process is important to facilitate the improvement of human performance. With the important assumption that individual behavior (mantees and mentors) can be changed as it is aware of each individual is obliged to continuously learn (long life learner). Keywords: Mentoring, Performance Improvement, Innovation